1982
DOI: 10.1073/pnas.79.7.2379
|View full text |Cite
|
Sign up to set email alerts
|

Human lung small-cell carcinoma contains bombesin.

Abstract: The presence of immunoreactive bombesin in a human lung small-cell carcinoma grown in nude mice was established by several criteria: (i) Radioimmunoassay of tissue extracts for bombesin revealed approximately 6.5 pmol/g of tissue; (ii) bombesin was found in 12-14% of the tumor cells by immunohistochemical localization; (iii) gel filtration ofsmall-cell carcinoma extract on Sephadex G-75 and Bio-Gel P-4 gave only a single peak ofimmunoreactivity, which occurred at the elution volume ofbombesin; and (iv) reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(54 citation statements)
references
References 39 publications
0
54
0
Order By: Relevance
“…Since human SCCL and SCCL-derived cell lines are known to synthesize and secrete bombesin-like peptides (Erisman et al, 1982;Moody et al, 1983;Sorenson et al, 1982), it is possible that these peptides may function as autocrine growth factors involved in the abnormal growth of the tumours. Evidence in favour of this proposition has been reported by Cuttitta et al (1985), who showed that a highly specific monoclonal antibody against bombesin markedly suppressed the growth of SCCL cells both in vitro and in nude mice.…”
Section: Introductionmentioning
confidence: 99%
“…Since human SCCL and SCCL-derived cell lines are known to synthesize and secrete bombesin-like peptides (Erisman et al, 1982;Moody et al, 1983;Sorenson et al, 1982), it is possible that these peptides may function as autocrine growth factors involved in the abnormal growth of the tumours. Evidence in favour of this proposition has been reported by Cuttitta et al (1985), who showed that a highly specific monoclonal antibody against bombesin markedly suppressed the growth of SCCL cells both in vitro and in nude mice.…”
Section: Introductionmentioning
confidence: 99%
“…Spindel et al (1984) prepared and cloned cDNAs derived from mRNA from a human pulmonary carcinoid tumour that had strong immunoreactivity to GRP. A number of investigators have reported that immunoreactive GRP is present in the fetal and neonatal lung (Wharton' et al, 1978;Yamaguchi et al, 1983) and in primary lung cancer, especially in SCLC (Erisman et al, 1982;Moody et al, 1981;Wharton et al, 1978). Additionally, immunohistochemical analysis (Cuttitta et al, 1988) of ProGRP fragments (GGAPs) was also reported to immunostain both GRP and GGAP in SCLC cell lines and human SCLC tumours.…”
mentioning
confidence: 99%
“…SCLC is known to secrete bombesin-like peptides (20)(21)(22) that might act as autocrine growth factors (2,25). Thus it was plausible but not proven that an antagonist to bombesin/GRP would inhibit SCLC growth, so we tested the effects of peptides A and D on SCLC cells in vitro.…”
Section: Peptide a And Peptide D Inhibit The Growth Of Sclc Cellmentioning
confidence: 99%
“…SCLC constitutes 25% of lung cancers and is, therefore, of major clinical and economic importance. Evidence that bombesin-like peptides, which are secreted by these tumors (20)(21)(22), can act as autocrine growth factors (25) has prompted the search for clinically useful GRP antagonists. We have presented evidence that two peptides that are antagonists of GRP and vasopressin profoundly inhibit the growth of SCLC cells in vitro although the participation of other growthpromoting peptides cannot be excluded.…”
Section: Peptide a And Peptide D Inhibit The Growth Of Sclc Cellmentioning
confidence: 99%
See 1 more Smart Citation